Biosensor for integrin inhibition of mammalian cell adhesion and migration using micropatterned cell culture substrate and retroreflective optical signaling - Kyung Won Lee; Eun Kyeong Yang; Duc Long Nguyen; Soo A Park; Moon Suk Kim; Jae-Ho Kim; Min Young Lee; Hyun C. Yoon (Sensing and Bio-Sensing Research)
Integrins are a family of transmembrane receptors that play a crucial role in cell adhesion and migration. Integrins can uniquely transduce biochemical signals bidirectionally across the membrane and physically link the cell-cell and cell-extracellular matrix (ECM) with ligand bonds. The arginyl-glycyl-aspartic acid (RGD) peptide motif is present in the ECM as a minimal recognition sequence for integrins. To leverage this property in cell-based therapy, RGD variants, such as cyclic-type RGDfK (c(RGDfK)), which share a similar structure with RGD but exhibit a higher affinity for integrins, have been developed. However, because most evaluation methods for newly developed RGD variants focus on affinity strength, tools for cellular effects are required. In this study, we developed a new platform that integrates micropatterned three-dimensional cell culture substrates with a non-spectroscopic optical analysis system to quantitatively analyze the effects of RGD variants on cell adhesion and migration. The specially micropatterned substrate provides a cell adhesive and migration area to provide a restricted analysis area. Owing to the characteristics of retroreflective Janus particles (RJPs), a non-spectroscopic optical analysis system provides long-term stable optical verification properties and a simple optical setup. These techniques were integrated to quantitatively determine the integrin inhibitory effect of various concentrations of RGD variant. To demonstrate the efficacy of the developed cellular level RGD variant testing platform, the model cell line L929 fibroblast and model RGD variant c(RGDfK) were analyzed ranging from 0 to 10 μM. The results showed that the developed system could effectively and quantitatively analyze the effects of RGD variants on cells across various concentrations.